Synergistic enhancement of CO2 adsorption performance of porous biochar by N/O heteroatoms and pore structure: Experiment and DFT simulation - Zhipei Tang; Ju Zhu; Ziqi Zhao; Heming Dong; Qian Du; Dongdong Feng; Yu Zhang; Tianhang Zhang; Yirui Peng; Jianmin Gao; Min Xie (Journal of Environmental Chemical Engineering, 2025)

Internal electric field and atomic-level interface modulation of V-MoS2/ZnIn2S4 heterojunction for efficient photocatalytic Uranium(VI) removal - Zhijian Zheng; Zifang Ye; Haiwei Qiu; Hongyi Wang; Xizao Wang; Heming Zhu; Zhian Wang; Youqun Wang; Zhimin Dong; Zhibin Zhang; Yibao Liu; Yunhai Liu (Journal of Environmental Chemical Engineering, 2025)

Identification of the CYP gene family: insights into carotenoid metabolism associated with red shell in Meretrix meretrix - Heming Shi; Lulu Fu; Yinghui Dong; Zhihua Lin; Jilin Xu; Hanhan Yao (Aquaculture International, 2025)

Prediction of Pharmacoresistance in Drug-Naïve Temporal Lobe Epilepsy Using Ictal EEGs Based on Convolutional Neural Network - Yiwei Gong; Zheng Zhang; Yuanzhi Yang; Shuo Zhang; Ruifeng Zheng; Xin Li; Xiaoyun Qiu; Yang Zheng; Shuang Wang; Wenyu Liu; Fan Fei; Heming Cheng; et al. (Neuroscience Bulletin, 2025)

Investigation of instability characteristics and lean-burn limit of methane/air laminar premixed flames at sub-atmospheric pressure - Xiao Yang; Jianmin Gao; Hao Wang; Min Xie; Qian Du; Yu Zhang; Dongdong Feng; Heming Dong; Ziqi Zhao (Fuel, 2025)

Investigation of NO emission characteristics from co-combustion of methane and ammonia at high-altitude areas - Xiao Yang; Jianmin Gao; Biao Huang; Shijiu Ma; Min Xie; Qian Du; Yu Zhang; Heming Dong (Journal of Hazardous Materials, 2025)

The synergistic influence mechanism of the alkali metal sodium and CO2 on coal rapid pyrolysis soot: Experiments and DFT calculations - Ziqi Zhao; Jirui Jin; Qian Du; Dun Li; Jianmin Gao; Heming Dong; Yu Zhang; Di Wu; Xiao Yang (Fuel, 2025)

Targeted construction of porous biochar with well-developed pore structure for high-performance CO2 adsorption - Zhipei Tang; Jianmin Gao; Heming Dong; Qian Du; Dongdong Feng; Jian Cheng; Junfeng Li; Yirui Peng; Tianhang Zhang; Min Xie; Huanlong Chen (Journal of Environmental Chemical Engineering, 2024)

A simple projection method to correlate the principal mechanical direction with the principal microstructural direction of human osteoporotic femoral heads - Heming Chen; Dong Wang; Jiayi Li; Qingqiang Yao; Nicola M. Pugno; Zhiyong Li; Qiang Chen (Medical & Biological Engineering & Computing, 2024)

Research on NO generation characteristics of ammonia-premixed flame - Qiaoqun Sun; Yukai Li; Yu Zhang; Jianmin Gao; Heming Dong; Dongdong Feng; Zheng Chen; Shaozeng Sun (Science of The Total Environment, 2023)

Characterization and Function Analysis of β, β-carotene-9′, 10′-oxygenase 2 (BCDO2) Gene in Carotenoid Metabolism of the Red Shell Hard Clam (Meretrix meretrix) - Lulu Fu; Heming Shi; Wenfang Dai; Hanhan Yao; Yongbo Bao; Zhihua Lin; Yinghui Dong (Frontiers in Marine Science, 2021)
The relationship between carotenoid and shellfish shell color has gained increasing attention. β, β-carotene-9′,10′-oxygenase 2 (BCDO2) is a key enzyme in animal carotenoid metabolism, and its accumulation affects the change in body color, as demonstrated in mammals, birds, and fish. However, it is unclear whether BCDO2 is involved in the formation of the red shell color of clam. To explore the molecular structure and biological function of BCDO2 gene in the process of carotenoids accumulation, in this study, the BCDO2 from hard clam Meretrix meretrix (designated as Mm-BCDO2 ) was cloned and characterized, and the single-nucleotide polymorphisms (SNPs) associated with shell color were detected. The results of qRT-PCR indicated that Mm-BCDO2 gene was expressed in all six tested tissues, and the expression of mantle was significantly higher than other tissues ( P < 0.05). The association analysis identified 20 SNPs in the exons of Mm-BCDO2 , among which three loci (i.e., c.984A > C, c.1148C > T, and c.1187A > T) were remarkably related ( P < 0.05) to the shell color of clam. The western blot analysis revealed that the expression level of Mm-BCDO2 in the mantle of red shell clams was stronger than that of white shell clams ( P < 0.05). Further, the immunofluorescence analysis indicated that the single-layer columnar cells at the edge of the mantle were the major sites for the Mm-BCDO2 secretion. This study explored the potential impacts of BCDO2 gene on the shell color of M. meretrix , which provided a theoretical basis for a better understanding of the important role of BCDO2 in carotenoid metabolism.